EFEKTIVITAS PROMOSI DIGITAL BERBASIS MEDIA SOSIAL DALAM MEMBANGUN BRAND AWARENESS KONSUMEN PADA INDUSTRI KREATIF: STUDI EMPIRIS PADA JTWO VISUAL - Jasmine Nurul Asyifa; Yohana Ari Ratnaningtyas (Merwin Publisher, 2026)
The growth of digital technology has transformed marketing practices, encouraging businesses to utilize digital promotion to strengthen brand positioning. This study aims to examine the effect of digital promotion on consumer brand awareness of Jtwo Visual in the creative service industry. The research employed a quantitative approach with a descriptive research design. Data were collected using a questionnaire distributed to 51 respondents selected through purposive sampling, consisting of consumers who had used Jtwo Visual services. The instrument used a 5-point Likert scale to measure the main variables: digital promotion as the independent variable and brand awareness as the dependent variable. Data analysis was conducted using simple linear regression to test the relationship between variables. The results indicate that digital promotion has a significant positive effect on brand awareness with a regression coefficient of 0.988 and a significance value of p < 0.05. The correlation coefficient (R) of 0.876 indicates a strong relationship, while the coefficient of determination (R²) of 0.768 shows that 76.8% of brand awareness variation can be explained by digital promotion. Instrument reliability testing produced Cronbach’s Alpha values above 0.70, indicating acceptable reliability. The study is limited by the relatively small sample size and the focus on a single creative business. Practically, the findings highlight the importance of consistent and interactive digital promotion through social media to enhance brand awareness in the creative industry.